Construction of an Estimating System of Gear Noise using Thermography - UENISHI, Yasuhiro; HIROGAKI, Toshiki; KATAYAMA, Tutao; NAKANO, Yuusuke; AOYAMA, Eiichi; TANGE, Hiromi (Transactions of the Japan Society of Mechanical Engineers Series C, 2005)
We proposed a new estimating method of a high-speed and high accurate tooth contact by using thermography. This method has aimed to short the measurement time, and to know an accurate tooth contact area and the strength of the surface pressure by measuring the heat generated at the time of meshing gear teeth without contact. First, the radiation performance on the gear tooth surface was investigated as a basic experiment, and the effect of lubricantion was examined. Moreover, experimental conditions were researched. Next, the reliability of the present method for measuring the surface temperature distribution was evaluated by comparing with the result obtained by paints. The surface pressure on the tooth surface was estimated based on obtained temparature distribution on the gear tooth surface. Finally, we made an attempt to predict the gear meshing force based on the proposed estimating method.